(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The purpose of this study was to determine the reality of the team’s the study aimed to identify emotional intelligence and its relationship to developing the leadership capabilities of secondary school principals in Jeddah from the teachers’ point of view. The researcher used the quantitative, causal, and comparative survey method, and the study data was collected using a questionnaire of 59 statements, which was distributed to a sample of male and female teachers at the secondary level in Jeddah Governorate. The number of participants in the study was 526 male and female teachers, and the results of the study concluded that the degree of emotional intelligence and the degree of leadership abilities came with a degree of agreement (high). The study also found that there is a very strong (positive) positive relationship with statistical significance to the degree of emotional intelligence and the degree of leadership abilities among secondary school principals in Jeddah Governorate. The study found that there were statistically significant differences in the degree of emotional intelligence attributed to the gender variable, and these differences were in Favor of (female) teachers. While the study found that there were no statistically significant differences regarding the degree of leadership abilities due to the gender variable. The study found that there were no statistically significant differences regarding the degree of emotional intelligence and the degree of leadership abilities due to the variables of academic qualification and years of experience. Based on the analysis of the results of the study, a number of proposals and recommendations were reached, the most important of which are training school principals to develop emotional intelligence skills and how to apply them in educational leadership, providing educational and awareness programs for school principals about the importance of emotional intelligence in improving leadership performance and interaction with the educational team and students, Adopting strategies and evaluation tools to measure and evaluate the level of emotional intelligence of school principals and providing the necessary support and development to improve it, which contributes to achieving high professional development and improving educational outcomes.